How to think about how to think about aesthetic value. Issue 1 (31st December 2022) - Lopes, Dominic McIver
ABSTRACT: Several art scholars have recently doubted the prudence of thinking about the nature of aesthetic value. The problem is that traditional thinking about aesthetic value fails to capture the specificities with which empirical art scholars must grapple. This paper diagnoses how the tradition came to think in this problematic way about aesthetic value. It then sketches an approach to aesthetic value that boosts the refractive power of the tools that scholars of the arts can use to bring into focus some of the specificities they care about. The path to that goal skirts the troublesome features of traditional approaches.